2011
DOI: 10.1111/j.1748-5827.2011.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine obesity: is there a difference between veterinarian and owner perception?

Abstract: This study confirms the important role of the vet in providing information about the issue of dog weight but also suggests that providing verbal information is sometimes insufficient. The study also indicates the potential value of qualitative research methods to further understand client perception of complex animal care issues and highlights the need for further in-depth research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 16 publications
9
76
0
4
Order By: Relevance
“…Approximately 50% of dogs are overweight, and approximately 20% are obese. 3,[5][6][7] Although there is no objective measure for obesity that is readily available to the general population, dogs with body weight 15% to 20% or more above ideal weight 5 can be assessed as obese, and obesity can be determined by use of a body composition scale such as the 9-point BCS system developed by researchers at Purina, which relies on physical examination, palpation, and a visual aid chart. 8 Certain breeds such as Labrador Retrievers and Beagles seem predisposed to obesity, 9 although obesity can develop in any purebred or mixed-breed dog.…”
mentioning
confidence: 99%
“…Approximately 50% of dogs are overweight, and approximately 20% are obese. 3,[5][6][7] Although there is no objective measure for obesity that is readily available to the general population, dogs with body weight 15% to 20% or more above ideal weight 5 can be assessed as obese, and obesity can be determined by use of a body composition scale such as the 9-point BCS system developed by researchers at Purina, which relies on physical examination, palpation, and a visual aid chart. 8 Certain breeds such as Labrador Retrievers and Beagles seem predisposed to obesity, 9 although obesity can develop in any purebred or mixed-breed dog.…”
mentioning
confidence: 99%
“…So, in the same way that parents of overweight children consistently underestimate their children's weight (Etelson and others 2003), a number of studies show that owners of overweight or obese dogs underestimate the body condition of their animals (Rohlf and others 2010, White and others 2011) and cats (Allan and others 2000, Kienzle and Bergler 2006). Furthermore, practising vets may fail to identify overweight animals.…”
Section: Human-animal Bondmentioning
confidence: 96%
“…If we consider pet weight loss, several components are necessary for success, beginning with recognition or awareness 40 of the problem on the part of the owner. 41 Indeed, changing the owner's behavior may be considered to be the most important component for the success of pet weight loss. 30,31 Furthermore, several studies have shown a link such that owners classified as overweight or obese were more likely to own an overweight or obese dog.…”
Section: Health Behavior Change Strategiesmentioning
confidence: 99%